AUTOMATIC CARVING TOOLS USING ARDUINO MICROCONTROLLER - Okta Andrica Putra (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
In carving crafts, there are a lot of motifs or regional characteristics from which the carvings originated, making a carving work requires special skills, patience, thoroughness, and full concentration so that there are no mistakes in carving. In today's technological developments, the manufacture of wood carving crafts using a CNC (Computer Numeric Control) carving machine has begun to shift the role of traditional carving craftsmen who are currently out of business, because the results of the CNC carving machines are much better and more detailed in carving, because of that work is a machine so an operator only enters certain codes into the machine computer, in operation a CNC carving machine operator must have special skills